Endovascular Treatment of 346 Middle Cerebral Artery Aneurysms: Results of a 16-Year Single-Center Experience. Issue 1 (January 2015) - Kadkhodayan, Yasha; Delgado Almandoz, Josser E.; Fease, Jennifer L.; Scholz, Jill M.; Blem, Anna M.; Tran, Kira; Crandall, Benjamin M.; Tubman, David E.
Abstract : BACKGROUND: The endovascular treatment of middle cerebral artery (MCA) aneurysms has been controversial because of the frequency of complex anatomy and the relative ease of surgical clipping in this location. OBJECTIVE: To present a large single-center experience with the endovascular treatment of MCA aneurysms. METHODS: The neurointerventional database at our institution was reviewed for all endovascular treatments of MCA aneurysms. Demographics, aneurysm characteristics, treatment modality, intraprocedural hemorrhagic and thromboembolic events, 30-day neurological events, and follow-up angiographic studies were recorded. RESULTS: From December 1996 to April 2013, 292 patients underwent endovascular treatment of 346 MCA aneurysms. Of these, 341 (98.6%) were successfully completed. Balloon neck remodeling was used in 230 procedures (66.5%). Ninety-five procedures (27.4%) were for ruptured aneurysms. The rate of intraprocedural hemorrhage was 2.6% (9 of 346). The overall rate of intraprocedural thromboembolic events was 13.6% (47 of 346), significantly more common in patients with acute subarachnoid hemorrhage (27.4%; P < .001). The 30-day major (modified Rankin Scale score > 2) neurological event rate was 2.9% (10 of 346), significantly more common in patients with subarachnoid hemorrhage (8.4%) compared with those without (0.8%; P < .001). The rate of complete or near-complete aneurysm occlusion at was 90.6% ≥ 6 months and 91.8% at ≥ 2 years, with an average of 24 months of follow-up available for 247 procedures. CONCLUSION: Endovascular treatment of MCA aneurysms can be safe and effective. However, it is associated with a high asymptomatic thromboembolic event rate that is more frequent in the setting of acute subarachnoid hemorrhage. ABBREVIATIONS: ISAT, International Subarachnoid Aneurysm Trial MCA, middle cerebral artery mRS, modified Rankin Scale SAH, subarachnoid hemorrhage TIA, transient ischemic attack